Questionning The Power of Subaltern In Nawal El Saadawi’s Novel Women At Point of Zero (1975) - Miloudia, Ikram; Boumous ,Moufida (Faculty of Letters and Foreign Languages Department of English, 2018)
In the context of Western feminist theory, this study explores Nawal El Saadawi's celebrated novel, Woman at Point Zero. The aim of this analysis is to establish the benefits of comparative feminist discourse with regard to patriarchal policies in the Middle East. El Saadawi challenges the hegemony of a traditionally phallocentric society empowered by masculinity. The woman at Point Zero by Nawal El-Saadawi is a novel that embodies the hard condition of a woman, named Firdaus, who struggles for her rights, not only as a woman but also as a human. In three chapters, this study will provide a framework of post colonial theory in the first chapter. The second chapter will shed light on the contributions of Arab Women who support many voiceless women. The last one will be devoted to the analysis of Nawal al-Saadawi novel Woman At The Point Zero(1975) with respect to the aforementioned theories